Inventing the New Negro : Narrative, Culture, and Ethnography - Lamothe, Daphne Mary (Book collections on Project MUSE., 2008)
Daphne Lamothe explores how many black writers and intellectuals in the early twentieth century adapted ethnography and folklore in their narratives to create a cohesive, collective, and modern Black identity.